Estimation of Facial Attractiveness as Biomarker of Ovulation Using Facial Photogrammetry during Phases of Female Sexual Cycle - , Ibinabo Fubara Bob-Manuel; , Adaobi Linda Okerulu; , Osah Martins Onwuka (Archives of Current Research International, 2023)
Background: Facial photogrammetry during various phases of female sexual cycle was used to estimate the facial beauty/attractiveness of females at menstruation and ovulation phase of their monthly cycle; in order to form basis of using facial attractiveness as a biomarker of ovulation. Methods: Thirty-seven (37)volunteered female scholars in an institution in Southern Nigeria were purposively selected to include menstruating females of 17 – 28 years. Photographs of the selected subjects were taken during menstruation and two weeks after menstruation (ovulation period). Afterwards, photogrammetric analysis was performed; 350 males were asked to pick preferred facialpicture of each of the subjects. Results: There was significant differences between the facial proportions measured during the sexual cycle and ideal facial proportion of the subjects p<0.05. The estimation of attractiveness was higher in ovulation phase as there was positive significant correlation of facial proportions of the subjects during the various phases of their sexual cycle. Conclusion: The findings suggests that facial beauty/attractiveness may be used to estimate the sexual cycle of females as enhanced facial beauty/attractiveness could be a biomarker of ovulation.